Global, regional and national burden of traumatic brain injury and spinal cord injury, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019 - Guan, Bin; Anderson, David B; Chen, Lingxiao; Feng, Shiqing; Zhou, Hengxing (BMJ open, 2023)
ObjectivesTo evaluate the most up-to-date burden of traumatic brain injury (TBI) and spinal cord injury (SCI) and analyse their leading causes in different countries/territories.DesignAn analysis of Global Burden of Disease (GBD) data.SettingThe epidemiological data were gathered from GBD Results Tool (1 January, 1990─31 December 2019) covering 21 GBD regions and 204 countries/ territories.ParticipantsPatients with TBI/SCI.Main outcomes and measuresAbsolute numbers and age-standardised rates/estimates of incidence, prevalence and years lived with disability (YLDs) of TBI/SCI by location in 2019, with their percentage changes from 1990 to 2019. The leading causes (eg, falls) of TBI/SCI in 204 countries/territories.ResultsGlobally, in 2019, TBI had 27.16 million new cases, 48.99 million prevalent cases and 7.08 million YLDs. SCI had 0.91 million new cases, 20.64 million prevalent cases and 6.20 million YLDs. Global age-standardised incidence rates of TBI decreased significantly by −5.5% (95% uncertainty interval −8.9% to −3.0%) from 1990 to 2019, whereas SCI had no significant change (−6.1% (−17.3% to 1.5%)). Regionally, in 2019, Eastern Europe and High-income North America had the highest burden of TBI and SCI, respectively. Nationally, in 2019, Slovenia and Afghanistan had the highest age-standardised incidence rates of TBI and SCI, respectively. For TBI, falls were the leading cause in 74% (150/204) of countries/territories, followed by pedestrian road injuries (14%, 29/204), motor vehicle road injuries (5%, 11/204), and conflict and terrorism (2%, 4/204). For SCI, falls were the leading cause in 97% (198/204) of countries/territories, followed by conflict and terrorism (3%, 6/204).ConclusionsGlobal age-standardised incidence rates of TBI have decreased significantly since 1990, whereas SCI had no significant change. The leading causes of TBI/SCI globally were falls, but variations did exist between countries/territories. Policy-makers should continue to prioritise interventions to reduce falls, but priorities may vary between countries/territories.